Safety device strength analysis during repair of cylinder loader up down curing machine - Rizky Fajar Sutrimo; Muhamad Fitri (JTTM : Jurnal Terapan Teknik Mesin, 2025)
While repairing the up-down loader cylinder by the tire company engineering team, a work accident occurred. The loader fell due to movement when releasing the loader cylinder and the loader load which was hanging on the nok, because it was not strong enough to support the loader, the nok fell off followed by the loader dropping. So then the engineering team installed a safety device to withstand the load of the loader if something similar happened, but until now its strength has not been tested. The aim of this research is to analyze the strength of the safety device installed on the loader using calculation analysis and test simulations with Finite Element Analysis (FEA). The research began with collecting load data received by the safety device, then carrying out theoretical calculation analysis and simulations using Solidwork software. And the result it by calculating maximum bending stress is 63,30 N/mm2 . Meanwhile, for the strength of the welded joint 424,05 kN, while the actual load received by the welded joint is 6806,891 N. So it can be stated that the welded joint is safe. In the loading simulation using Solidwork software, the maximum stress (57,279 N/mm2), the maximum deformation (0.036mm), and the FOS (4,365). Safety loaders with ASTM A36 material are declared safe because the FOS value is > 2 (safety factor based on static load)